2021
DOI: 10.3389/feart.2021.698347
|View full text |Cite
|
Sign up to set email alerts
|

Ore-Forming Fluid Evolution of Shallow Polyhalite Deposits in the Kunteyi Playa in the North Qaidam Basin

Abstract: Polyhalite occurrence in the Kunteyi Playa in the Qaidam Basin has been known for many years. However, the genetic mechanism of this deposit remains unclear. In this study, a typical section in the playa depocenter is selected to study the polyhalite mineralogy combined with the homogenization temperature and composition of halite fluid inclusions in shallow evaporitic strata. The results show that 1) the main evaporite minerals in the strata are halite and polyhalite; no common gypsum is found; 2) analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A large amount of polyhalite is buried in the Pleistocene strata of Kunteyi. However, this mineral is difficult to develop because of its insoluble characteristics and deeply buried layers (Yuan et al, 2021). All brines analyzed in this study were collected during the Holocene, and it needs to be further confirmed whether polyhalite buried in the Pleistocene can influence K + and Mg 2+ concentrations in the superficial layer.…”
Section: Chemical Evolution Of the Brinementioning
confidence: 93%
“…A large amount of polyhalite is buried in the Pleistocene strata of Kunteyi. However, this mineral is difficult to develop because of its insoluble characteristics and deeply buried layers (Yuan et al, 2021). All brines analyzed in this study were collected during the Holocene, and it needs to be further confirmed whether polyhalite buried in the Pleistocene can influence K + and Mg 2+ concentrations in the superficial layer.…”
Section: Chemical Evolution Of the Brinementioning
confidence: 93%